Evaluasi Akurasi Metode Arus Cabang Melalui Pendekatan Teoritis, Simulasi EWB, dan Pengukuran Eksperimental - Ariyen Duri'; Martina Pineng; Martati Martati (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2025)
This study aims to evaluate the accuracy of the branch current analysis method through three approaches: theoretical calculation, simulation using Electronics Workbench (EWB), and experimental measurement using a digital multimeter. The test circuit consists of two 10 V DC voltage sources and three resistors (R1 = 2200 Ω, R2 = 2200 Ω, R3 = 1000 Ω) forming two loops with three branch currents (I1, I2, I3). The theoretical analysis was performed by applying Kirchhoff’s Current Law (KCL) and Kirchhoff’s Voltage Law (KVL), while the simulation was conducted in EWB software with the same configuration. Direct measurements were obtained by connecting the multimeter in series with each branch. The results show that the simulated current values closely match the theoretical calculations, with a maximum relative error of 0.0084% and an accuracy of 99%. Meanwhile, the experimental measurements exhibit larger deviations compared to the simulation, ranging from 1% to 2 %, with accuracies between 97% and 98%. Overall, the study demonstrates that the branch current method produces consistent results between theoretical calculations and simulations, while the experimental measurements show deviations that remain within acceptable limits due to component tolerances, connection resistance, and instrument accuracy.